Ontogenetic allometry of the postcranial skeleton of the giraffe (Giraffa camelopardalis) with application to giraffe life history evolution and palaeontology - Mitchell, Graham (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2015.